RECONSTRUCTING THE LEGAL FRAMEWORK OF TRADE SECRET PROTECTION VIS-À-VIS CYBER THEFT: A Cross-Jurisdictional Comparative Study - Disemadi, Hari Sutra; Chutia, Upankar; Afdal, Windi; Taniady, Vicko; Tan, David (Fakultas Syariah, 2025)
The growing incidence of cyber theft has exposed critical deficiencies in trade secret protection regimes, particularly in jurisdictions lacking integrated cybersecurity measures. This study analyses the legal frameworks of Indonesia, India, and Australia, using the United States' Defend Trade Secrets Act (DTSA) as a benchmark to evaluate their capacity to address digital trade secret misappropriation. Employing a comparative legal methodology, it examines statutory provisions, judicial interpretations, and enforcement mechanisms relevant to cybersecurity threats. The findings reveal that while Indonesia has enacted a trade secret statute, it lacks procedural safeguards specifically designed to address cyber theft. India and Australia, by contrast, depend on disjointed protections rooted in contract law, breach of confidence, and general cybercrime statutes. None of the jurisdictions provide a robust legal framework incorporating vital cybersecurity components such as ex-parte seizure, digital evidence management, or encryption standards. These shortcomings highlight a critical vulnerability in safeguarding proprietary information amidst escalating cyber threats. The study underscores the urgent need for legislative reform to align trade secret protection with contemporary cybersecurity challenges. Its insights contribute to the ongoing academic and legal discourse on the adequacy of current laws in mitigating cyber-enabled intellectual property violations. Meningkatnya insiden pencurian siber telah mengungkap kelemahan mendasar dalam rezim perlindungan rahasia dagang, terutama di yurisdiksi yang belum mengintegrasikan langkah-langkah keamanan siber dalam kerangka hukumnya. Studi ini menganalisis sistem hukum Indonesia, India, dan Australia, dengan membandingkannya terhadap Defend Trade Secrets Act (DTSA) dari Amerika Serikat untuk menilai efektivitasnya dalam menangani penyalahgunaan rahasia dagang secara digital. Dengan pendekatan hukum komparatif, kajian ini mengevaluasi ketentuan undang-undang, doktrin yurisprudensi, dan mekanisme penegakan yang relevan terhadap ancaman siber. Hasilnya menunjukkan bahwa meskipun Indonesia memiliki undang-undang khusus, perlindungan prosedural terhadap pencurian siber belum memadai. India dan Australia justru mengandalkan perlindungan yang terfragmentasi melalui hukum kontrak, asas kepercayaan, dan regulasi kejahatan siber umum. Tidak satu pun dari ketiga negara menyediakan kerangka hukum menyeluruh yang mencakup unsur penting seperti penyitaan ex-parte, pengelolaan bukti digital, atau standar enkripsi. Kekosongan ini menunjukkan lemahnya perlindungan terhadap informasi bisnis sensitif di tengah meningkatnya ancaman digital. Studi ini menekankan urgensi reformasi legislatif untuk menyelaraskan perlindungan rahasia dagang dengan tantangan keamanan siber modern. Temuan ini memberi kontribusi penting bagi wacana akademik dan hukum terkait perlindungan kekayaan intelektual di era digital.